Precision procedures and the application of artificial intelligence in cattle breeding with special reference to the identification of beef cattle - Tarr, Bence; Katona, Balázs; Szabó, István; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
Artificial Intelligence (AI) has become an important tool for optimising breeding processes in several areas of animal production. In this thesis, we have presented examples from the literature, mainly for the identification and counting of cattle. The individual identification of animals, the monitoring of their behaviour and the control of their movements support a number of conclusions from both an animal welfare and a veterinary point of view. Automation of the processing of captured images has also become essential. This process is supported by Artificial Intelligence. Deep learning and neural networks are excellent tools for segmenting images and processing their content based on different features. Convolutional neural networks are specifically powerful for such tasks and we have seen that further developments of these networks (e.g. Faster R-CNN) allow even more efficient image analysis procedures. Processing animal images can be a major step forward for automatic analysis and identification of livestock.
Keywords: image capturing; individual identification; artificial intelligence; neural network